1999
DOI: 10.1046/j.1523-5394.1999.07204.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Mammography Practice by African American Women

Abstract: These results demonstrate that intensive, community-based, culturally sensitive educational programming incorporating the spiritual environment of the faith community, such as the Witness Project, can positively influence breast cancer screening behaviors among rural, underserved African American women. Through the use of community churches and cancer survivors, breast cancer screening activities can be improved in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 30 publications
1
91
0
Order By: Relevance
“…46 Previous studies examining intervention efficacy, primarily among minority populations in urban settings but also (in one study) among rural African American women, have shown increased rates of mammography use. [25][26][27][28][29][30][31][32]47,48 Although the term efficacy is used in various ways, 38,49 community-based efficacy trials generally measure behavior change among individuals recruited to the study and exposed to the intervention. Community-based effectiveness trials, in contrast, measure behavior change in the community, regardless of exposure to the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…46 Previous studies examining intervention efficacy, primarily among minority populations in urban settings but also (in one study) among rural African American women, have shown increased rates of mammography use. [25][26][27][28][29][30][31][32]47,48 Although the term efficacy is used in various ways, 38,49 community-based efficacy trials generally measure behavior change among individuals recruited to the study and exposed to the intervention. Community-based effectiveness trials, in contrast, measure behavior change in the community, regardless of exposure to the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrating both triangulation and the translation of theory into practice is one of the most widely replicated mammography interventions, the Witness Project ® (91), which was based on a combination of the HBM, SLT, TTM, and locus of control targeting African American women in the South (36,38). In addition to principles and constructs from these theories, Erwin (an anthropologist) and colleagues conducted key informant interviews, participant observations, and focus groups (37) to develop this church-based intervention in which "witness role models" (breast and cervical cancer survivors) presented their personal experiences in a spiritual context emphasizing early detection.…”
Section: Triangulation Exemplarsmentioning
confidence: 99%
“…In a Witness Project pilot study, self-reported BSE and mammography rates increased significantly from baseline to 6-month follow-up among women who had attended a Witness session (Erwin, Spatz, Stotts, & Hollenberg, 1999). In a recent qualitative evaluation of the Witness Project, the sessions were reported to be well-received by attendees largely because the Witness role models were seen as coming from their own social and cultural network, and were trusted (Bailey, Erwin, & Belin, 2000).…”
Section: Church-based Health Education Programsmentioning
confidence: 99%